Pro Poor Budgeting: Analysis of Budget Policies by the Social Affairs Office of Bojonegoro Regency for Poverty Reduction - Miftahul Huda, Muhammad; Kumalasari, Ana; Sofitasari (Journal of Governance and Administrative Reform, 2024)
Abstract Poverty remains a major development issue in Bojonegoro Regency. According to data from the Central Statistics Agency (BPS), the poverty rate in Bojonegoro reached 12.21% in 2022. This figure is still far from the poverty reduction target set in the Bojonegoro Regency Regional Medium-Term Development Plan (RPJMD), which aims for 11.55%. Additionally, Bojonegoro’s poverty rate remains in the red zone, exceeding both the national poverty average of 9.54% and the provincial average of East Java (10.38%). This study adopts Fredolin Berek et al.'s (2006) Pro Poor Budgeting model, which outlines three criteria for pro-poor budgets: (1) budgets that emphasize development policies favoring the poor; (2) budget practices and policies intentionally designed to create programs and projects aimed at the interests of the poor; and (3) budget policies that improve welfare and fulfill the basic rights of the poor. The findings reveal that the Bojonegoro Regency Government demonstrates a commitment to poverty alleviation, as reflected in its development planning documents with annual poverty reduction targets. However, these targets have not been achieved. The government lacks consistency in managing its Regional Budget (APBD), with salary expenditures surpassing allocations for poverty reduction priorities. The government’s primary focus remains on infrastructure development. Budget allocations directly addressing poverty reduction through accelerated household economic improvement and essential needs provision for poor households remain insufficient.  Keywords: Pro Poor Budgeting, Budget Policy, Poverty   Abstrak Kemiskinan hingga saat ini masih jadi masalah utama pembangunan di Kabupaten Bojonegoro. Bersumber Badan Pusat Statistik (BPS), jumlah penduduk miskin Bojonegoro pada tahun 2022 12,21 persen. Angka ini masih jauh dari target penurunan kemiskinan yang ditetapkan dalam Rencana Pembangunan Jangka Menengah Daerah (RPJMD) Kabupaten Bojonegoro, sebesar 11,55 persen. Selain itu, kemiskinan Bojonegoro masih kelompok zona merah dikarenakan jumlah kemiskinannya masih di atas rata-rata kemiskinan nasional yakni sebesar 9,54 persen dan Provinsi Jawa Timur (Jatim) sebesar 10,38 persen. Penelitian menggunakan teori Pro poor Budgeting model Fredolin Berek dkk. (2006) yang memberi tiga kriteria anggaran pro poor: Pertama, suatu anggaran yang mengarah pada pentingnya kebijakan pembangunan yang berpihak pada orang miskin. Kedua, praktik penyusunan dan kebijakan di bidang anggaran yang sengaja (by designed) ditujukan untuk membuat kebijakan, program dan proyek yang berpihak pada kepentingan masyarakat miskin. Ketiga, kebijakan anggaran yang dampaknya dapat meningkatkan kesejahteraan, termasuk juga terpenuhinya kebutuhan hak-hak dasar masyarakat miskin. Hasil penelitian menunjukkan, Pemerintah Kabupaten Bojonegoro sudah memiliki komitmen dalam pengentasan kemiskinan yang tertuang dalam dokumen perencanaan pembangunan memiliki target penurunan angka kemiskinan tahunan, namun target tersebut tidak tercapai, Pemerintah Kabupaten Bojonegoro kurang konsisten dalam membuat kebijakan pengelolaan APBD, belanja Gaji masih lebih tinggi dibandingkan belanja prioritas pengurangan kemiskinan, fokus utama pemerintah juga masih pembangunan infrastruktur. Anggaran APBD yang berdampak langsung pada penguarangan angka kemiskinan dengan mengakselerasi ekonomi Rumah Tangga Miskin, dan alokasi anggaran untuk mengurangi belanja orang miskin, khususnya  dalam pemenuhan kebutuhan dasar Rumah tangga miskin yang masih sangat kecil. Kata kunci: Pro Poor Budgeting, Kebijakan Anggaran, Kemiskinan.